Experimental study of the complex reflection coefficient of shear waves from the solid-liquid interface - Franco, Ediguer E.; Adamowski, Julio C.; Higuti, Ricardo T. [UNESP]; Buiochi, Flávio (Elsevier, 2010)
The determination of the reflection coefficient of shear waves reflected from a solid-liquid interface is an important method in order to study the viscoelastic properties of liquids at high frequency. The reflection coefficient is a complex number. While the magnitude measurement is relatively easy and precise, the phase measurement is very difficult due to its strong temperature dependence. For that reason, most authors choose a simplified method in order to obtain the viscoelastic properties of liquids from the measured coefficient. In this simplified method, inconsistent viscosity results are obtained because pure viscous behavior is assumed and the phase is not measured. This work deals with an effort to improve the experimental technique required to measure both the magnitude and phase of the reflection coefficient and it intends to report realistic values for oils in a wide range of viscosity (0.092 - 6.7 Pa.s). Moreover, a device calibration process is investigated in order to monitor the dynamic viscosity of the liquid.
Keywords: Reflection coefficient; Shear waves; Solid-liquid interface; Viscoelasticity; Complex number; Complex reflection coefficient; Device calibration; Dynamic viscosities; Experimental studies; Experimental techniques; High frequency; Magnitude measurement; Reflection coefficients; Simplified method; Solid-liquid interfaces; Temperature dependence; Viscoelastic properties; Elasticity; Intensive care units; Liquids; Phase measurement; Reflection; Shear flow; Ultrasonics; Viscosity; Phase interfaces